1976
DOI: 10.1111/j.1365-2427.1976.tb01647.x
|View full text |Cite
|
Sign up to set email alerts
|

Experiments on feeding and growth of the amphipod Gammarus pulex (L.) related to its distribution in the River Duddon

Abstract: Individuals of Gammarus pulex were kept at 15°Cfor periods of 23-70 days on diets comprised of elm or oak leaves, Tricladium and Clavariopsis {Hypho-mycete fungi), Molinia (grass), Zygogonium (alga), Nardia (liverwort). Both the mean interval between moults (mt), and daily increments in body wet weight, were related to diet. The lowest value for mi was 14-6 days on a diet of naturally decaying elm and oak leaves. The largest weight gains also occurred on this diet; the average daily gain in weight (Dw) = 130'8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
74
1

Year Published

1995
1995
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(77 citation statements)
references
References 19 publications
2
74
1
Order By: Relevance
“…G. pulex is a detrivore whose diet includes lignocellulose. Although this species prefers partially decayed material, it is able to survive on diets of undecayed or "inactivated" leaf litter (40,41). The hepatopancreas of G. pulex has been shown to contain endogenous cellulase (and phenoloxidase) activities that are not due to bacterial endosymbionts (41).…”
Section: And Coptotermes Formosanus (Bab40696) Gastropod Sequences Imentioning
confidence: 99%
“…G. pulex is a detrivore whose diet includes lignocellulose. Although this species prefers partially decayed material, it is able to survive on diets of undecayed or "inactivated" leaf litter (40,41). The hepatopancreas of G. pulex has been shown to contain endogenous cellulase (and phenoloxidase) activities that are not due to bacterial endosymbionts (41).…”
Section: And Coptotermes Formosanus (Bab40696) Gastropod Sequences Imentioning
confidence: 99%
“…However, workers such as Nilsson [11] found that, at 15 • C, an average of 1928.7 calories were produced from alder leaves g −1 day −1 , which is considerably greater than other leaves, for example, beech (197.6 calories were produced from beech leaves g −1 day −1 ). The growth rate for Nilsson's smaller G. pulex specimens, which were fed on alder leaves was similar to the rate of 130.8 µg day −1 at 15 • C obtained by Willoughby and Sutcliffe [1] with a diet of oak and elm.…”
Section: Introductionmentioning
confidence: 52%
“…Bacteria and fungi are important components of the detritivore diet [1], G. pulex and A. aquaticus both discriminated between fungal mycelia and either fungally colonized or uncolonized leaf material [9], which was illustrated by this study. The results clearly demonstrate that both species of macroinvertebrates preferred a diet of conditioned leaf material over unconditioned leaves, with natural conditioning being the favoured conditioning option.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations